Relationship between Hormonal Contraception and Menstrual Cycle - Hidayatul Kurniawati; Afifatul Latifah (HM Publisher, 2022)
Background: The high rate of baby births in Indonesia increase in population each year. Family planning is a way to regulate the number of children and birth spacing between children with contraception. Injection and pill contraceptives are hormonal contraceptives. However, the use of contraceptives has an impact on weight gain, nausea, vomiting, headaches, and swollen feet. Dusun Kepuk is one of the villages in the Bangsri sub-district with the domination used of hormonal contraception compared to other methods, and the side effects of using this hormonal contraceptive method are not known. The aim of the research was to determine the relationship between the use of hormonal contraceptives and changes in the menstrual cycle in Kepuk Village, Bangsri District, Jepara Regency. Methods: This was non-experimental research with a cross-sectional design conducted in Kepuk Village, Bangsri District, Jepara Regency. The population in this study were acceptors who used hormonal contraception (pills and injections). The samples were taken with purposive sampling based on the inclusion and exclusion criteria. This study used a questionnaire to obtain information from respondents. The data were analyzed using the SPSS chi-square correlation test. Results: Most respondents with 3 months of injected contraceptives suffer a disrupted menstrual cycle, as many as 51 respondents (71.8%). The Chi-Square test result p = 0.001 show that there is a relationship between the use of hormonal contraceptives and the menstrual cycle. Conclusion: The use of hormonal contraception is associated with changes in the menstrual cycle changes in Kepuk Village, Bangsri District, Jepara Regency.